Experimental sporotrichosis in a cyclophosphamide-induced immunosuppressed mice model. (26th October 2017) - Manente, Francine Alessandra; Quinello, Camila; Ferreira, Lucas Souza; de Andrade, Cleverton Roberto; Jellmayer, Juliana Aparecida; Portuondo, Deivys Leandro; Batista-Duharte, Alexander; Carlos, Iracilda Zeppone
Abstract: This report describes a model of host resistance for Sporothrix schenckii, an opportunistic fungi in immunosuppressed mice with cyclophosphamide (CY) to be used in studies of immunotoxicology and immunopharmacology. Two doses of CY were administered intraperitoneally: 200 mg/kg and a booster of 150 mg/kg at 9-day intervals. Three days after the first dose of CY the animals were infected subcutaneously with 1.8 × 10 8 yeast/ml ( S. schenckii ATCC 16345). At 7 and 14 days post-infection, the animals were euthanized and analyzed the fungal load by unit forming colony count in the spleen and popliteal lymph nodes. The relative weight of thymus and spleen, splenic index, the frequency of T and B cells in spleen by flow cytometry, the hind paw inflammation index and cytokine (interleukin [IL]-17, IL-10, and interferon [IFN]-γ) profile were measured. Histopathological studies of the spleen and the hind paw were also assessed. The immunosuppression status was confirmed at the evaluated days by reduction of relative weight of thymus, reduction of the splenic white pulp, the population of B and T lymphocytes, and the cytokine profile in the treated mice with CY in comparison with nontreated groups, associated to higher fungal load in hind paw and spleen in the infected mice. The described model reveals an increasing in susceptibility to infection and severity when associated with immunosuppression. This model can serve as a reference for studies of S. schenckii host resistance in pharmaceutical and toxicological studies.